Development of Application-Based Gamification for Illustration Drawing Material in Eighth Grade Junior High School Students - Friscana, Dhini; Prasetyo, Abdul Rahman (IJESS International Journal of Education and Social Science, 2025)
Learning at SMP Islam Sultan Agung Sudimoro uses a flipped classroom model due to the dense curriculum, with each topic covered in just 1–2 meetings. Students must study independently at home, but existing media like books and digital modules are seen as unappealing. To address this, a gamified, interactive illustration-based application was developed to boost interest and improve independent learning. This study aims to analyze students’ needs, develop the gamified media, and test its effectiveness in teaching cultural arts to eighth-grade students. The method used is R&D with the 4D model (Define, Design, Develop, Disseminate). The results show that students highly need interactive media. Expert validation of content and media achieved very valid scores (87.50% and 90.32%), practicality tests reached 93% (highly feasible), and the effectiveness test based on the N-Gain Score was 0.89 (high category). Thus, the application-based gamification was proven to be highly effective in helping students understand illustration drawing material.